Insecticide susceptibility analysis of Anopheles gambiae complex in Vlakbult, Mpumalanga 2012/13 - Koekemoer, Lizette (University of Pretoria, 2022)
Mini Dissertation (MPh (Public Health))--University of Pretoria, 2013.